Digital humanities: a mere label, or a field that the documentation sciences should bet on? - Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2013)
This paper aims to reflect the growing importance of the term "digital humanities", whether defined as a disciplinary field, a training profile or a movement linked to open access. Although closely related to library and information science, digital humanities is often used in projects without the collaboration of libraries. Developing specific support centres is one way to facilitate libraries’ cooperation and participation in digital humanities projects.